Assessment of Flood Awareness and Early Warning Systems: The Case of Beşikdüzü, Trabzon - Tuğçe Anılan; Hilal Durmuş; Emre Akçalı; Ömer Yüksek (Doğal Afetler ve Çevre Dergisi)
In this study, the flood, occurred in Beşikdüzü District, Trabzon, on 21 September 2016 and resulted in the large amount of life loss and property, was investigated in terms of hydrological and social aspects. For this purpose, firstly, various flood discharges for different return periods were estimated by regional flood frequency analysis in order to determine the flood quantile of the Beşikdüzü flood. Secondly, for determining flood risk awareness and needs in the early warning system, a survey was conducted with the people living in the region. Within the scope of general awareness, the people’s knowledge of the measures, strategies and policies implemented before, during or after the flood, was investigated. Within the scope of early warning awareness, the expectations of the people from early warning systems and their awareness on this issue were examined. The tendency to take action upon receiving early warnings or not, was evaluated on an event tree, and the factors depending on taking action were examined. At the end of the study, recommendations about early warning systems were also presented.